Flow of Mental Activity in Developing Dominant Representations for Solving Convergent Sequence Problems: Supporting Quality Education (SDG 4) - Nursupiamin Nursupiamin; Sukayasa Sukayasa; Muh. Rizal; Muhammad Ikram (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To investigate the flow of mental activities involved in developing dominant representations when solving convergent sequence problems and to understand how students transform dominant representations into alternative forms to support mathematical understanding. Method: Employing a qualitative case study approach involving 12 Mathematics Education students from the Faculty of Education and Teacher Training, Datokarama State Islamic University, Palu, who had completed real analysis courses and understood the concept of convergent sequences. Data were collected through validated tests and semi-structured interviews. The research procedure followed the stages proposed by Fraenkel et al., including phenomenon identification, participant selection, data collection, analysis, and interpretation. Results: The findings revealed that the flow of mental activities in developing dominant representations consists of five stages: understanding the problem, identifying dominant representations, converting dominant representations into alternative representations, evaluating and revising solutions, and reflecting on the effectiveness of the chosen representations. Students with verbal, visual, and symbolic dominant representations demonstrated different approaches in solving convergent sequence problems but followed a similar cognitive flow when transforming representations. Novelty: A systematic flow of mental activities for developing dominant representations in mathematical problem-solving. The findings contribute to mathematics education literature by explaining how representation transformation supports conceptual understanding of convergent sequences and promotes more effective learning practices aligned with the goals of quality education (SDG 4).